A Review of Immunotherapy for Stage III and Metastatic Non-Small Cell Lung Cancer and the Rationale for the ECOG-ACRIN EA5181 Study. (11th March 2021) - Varlotto, John M.; Sun, Zhuoxin; Ky, Bonnie; Upshaw, Jenica; Katz, Sharyn I.; Fitzgerald, Thomas J.; Wakelee, Heather; Diehn, Maximilian; Mankoff, David A.; Lovely, Christine; Belani, Chandra; Oettel, Kurt; et al.
Abstract : : ECOG-ACRIN EA5181 is a phase III prospective, randomized trial that randomizes patients undergoing chemo/radiation for locally advanced non-small cell lung cancer (LA-NSCLC) to concomitant durvalumab or no additional therapy, with both arms receiving 1 year of consolidative durvalumab. Radiation dose escalation failed to improve overall survival in RTOG 0617. However, conventionally fractionated radiation to 60 Gy with concomitant chemotherapy is associated with a high risk of local failure (38%–46%). It is hoped that concomitant immunotherapy during chemo/radiation can help decrease the risk of local failure, thereby improving overall survival and progression-free survival with acceptable toxicity. In this article, we review conventional chemo/radiation therapy for LA-NSCLC, as well as the quickly evolving world of immunotherapy in the treatment of non-small cell lung cancer and discuss the rationale and study design of EA5181. Implications for Practice: This article provides an up-to-date assessment of how immunotherapy is reshaping the landscape of metastatic non-small cell lung cancer (NSCLC) and how the impact of this therapy is now rapidly moving into the treatment of patients with locally advanced NSCLC who are presenting for curative treatment. This article reviews the recent publications of chemo/radiation as well as those combining immunotherapy with chemotherapy and chemo/radiation, and provides a strategy for improving overall survival of patients with locally advanced NSCLC by using concomitant immunotherapy with standard concurrent chemo/radiation. Abstract : This article reviews conventional chemo/radiation techniques for locally advanced non-small cell lung cancer (NSCLC) and the evolving field of immunotherapy in the treatment of NSCLC, focusing on the rationale and design of the ECOG-ACRIN EA5181 study.